Improving the damage tolerance of composite T-joints using shape memory alloy tufts. (May 2023) - Khor, Weeliam; Ravindran, Anil R.; Ciampa, Francesco; Ladani, Raj B.; Limprapuwiwattana, Manatsawee; Whitton, Pete; Foreman, Andrew D.; Meeks, Charlotte; Steele, Alan; Cooper, Tim; Rider, Andrew; Mouritz, Adrian P.
Abstract: This paper presents a novel approach to improve the structural properties and damage tolerance of fibre-reinforced polymer composite joints via tufting using shape memory alloy (SMA) filaments. T -shaped joints made of carbon-epoxy composite material were reinforced with thin SMA (Ni-Ti nitinol) tufts. Experimental testing and finite element (FE) modelling reveal that the ultimate load, ultimate displacement and absorbed energy capacity of the T -joint increase with the areal density of SMA tufts. Improvements of over 110% in strength and 450% in absorbed energy capacity were achieved by SMA tufting. Under certain conditions, the shape memory effect of the tufts can be activated via electrical resistance heating to partially or completely close cracks in the T -joint caused by over-loading. The novel use of SMA tufts both to improve the resistance against cracking and to close cracks when they occur is a unique approach to improving the damage tolerance of composite structural joints.